Science, society and the environment applying anthropology and physics to sustainability - Dove, Michael 1949-; Kammen, Daniel M. 1962- (Routledge, 2015)
In an era when pressing environmental problems make collaboration across the divide between sciences and arts and humanities essential, this book presents the results of a collaborative analysis by an anthropologist and a physicist of four key junctures between science, society, and environment. The first focuses on the systemic bias in science in favour of studying esoteric subjects as distinct from the mundane subjects of everyday life; the second is a study of the fire-climax grasslands of Southeast Asia, especially those dominated.